Crowdfunding Syariah: Model Pembiayaan Alternatif dalam Bingkai Fiqih: Sharia Crowdfunding: An Alternative Financing Model in the Framework of Contemporary Fiqh - Muhammad Adi Saputra; Muhammad Yazid (TIJARAH: Jurnal Ekonomi, Manajemen, dan Bisnis Syariah, 2025)
Sharia crowdfunding represents one of the innovative developments in Islamic financing systems in the digital era. This model offers an inclusive alternative financing method by involving the public directly in funding productive and social projects. Unlike conventional crowdfunding, Sharia crowdfunding emphasizes the principles of fiqh al-muʿāmalah, such as justice, transparency, and the prohibition of riba (usury), gharar (uncertainty), and maisir (speculation). This study aims to analyze Sharia crowdfunding from the perspective of contemporary Islamic jurisprudence (fiqh kontemporer), examine the contracts applied in its operation, and explore its relevance to the objectives of Islamic law (maqāṣid al-sharīʿah). The research adopts a qualitative, descriptive-analytical approach based on library research. The findings indicate that Sharia crowdfunding can serve as an effective and ethical alternative financing model aligned with Islamic law, provided it adheres to the principles of fairness, transparency, and strong Sharia supervision. Furthermore, it contributes to achieving socio-economic justice and financial inclusion in accordance with Islamic ethical values.